The power of legitimacy among nations - Franck, Thomas M. (Oxford University Press, 1990)
An authority on international law considers why it is that rules within the international system are for the most part obeyed, even though they are not usually enforced. The text uses practical examples to show how international law works successfully even without formal codes or laws.